10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Background Thyroid eye disease (TED) is an immune-mediated orbitopathy with an active inflammatory phase followed by quiescence. Reactivation after apparent quiescence is recognised but poorly characterised. We aimed to describe the incidence, timing, and phenotype of TED reactivation and explore potential risk factors and triggers. Methods Retrospective cohort study of 727 consecutive patients with TED (2015-2025). Reactivation was defined as new or worsening TED after ≥ 1 year of documented inactivity. Data included demographics, smoking status, interval from quiescence, phenotype, severity (EUGOGO), suspected precipitants, imaging, and treatment. Results Twenty-eight patients met reactivation criteria (3.9%, 95% CI 2.7%-5.5%), accounting for 29 episodes (one patient had two). Most were female (75%, 21/28). Mean age at reactivation was 60.2 ± 15.5 years (range 29-86); 75.9% of episodes occurred in patients ≥ 50 years (22/29). Median interval from quiescence to reactivation was 5 years (IQR 3-10, range 1-47). Extraocular muscle involvement occurred in 27/29 episodes (93.1%). Severity was mild (13/29, 44.8%), moderate-to-severe (12/29, 41.4%), or sight-threatening (4/29, 13.8%). Clear triggers were rare; thyroid dysfunction or positive thyroid antibodies were documented in 15/29 (51.7%). Management (recorded for 28 episodes) ranged from conservative care (15/28, 53.6%) to systemic corticosteroids (7/28, 25%), with less frequent immunomodulatory therapy (n = 3), orbital decompression (n = 3), and radiotherapy (n = 3). Conclusions TED reactivation occurred in 3.9% of patients, often within 5 years of quiescence, typically beyond the fifth decade, and most commonly with a muscle-predominant phenotype.